La formazione insegnanti oggi in prospettiva lifelong. Riflessioni e proposte per una scuola co-costruita e partecipata - Antonella Coppi (Studi sulla Formazione)
Italian Universities have been invested in new tasks and responsibilities in the teaching profession reformed access. New qualifying courses have been activated. “60 CFU” (DPCM 8/4/2023) course will be fully operative starting from June 2024. Teacher education, according to these regulatory actions, is moving toward a lifelong learning perspective that is increasingly necessary to promote update and increase the quality and effectiveness of learning (Dozza, Chianese, 2013). Professional profiles have to be change oriented and up to date in order to transform school into a community of participatory, co-constructed learning, adequate to cope with the growing need for integration and intercultural dialogue, specific and adapted to special needs, the use of information and communication technologies (TIC) for a school of the second millennium (Baldacci, 2019). This article offers a reflection on these issues relevance from a perspective of comparison and direct experiences in the field.